The intelligent lift: Artificial Intelligence's growing role in plastic surgery - a comprehensive review - Arkoubi, Amr Youssef (Frontiers in Surgery, 2025)
BackgroundArtificial Intelligence (AI) is rapidly transforming plastic surgery by enhancing diagnostic precision, surgical planning, and postoperative evaluation. Despite promising results in algorithmic performance, the clinical utility and ethical implications of AI in this specialty remain underexplored.MethodsThis study systematically reviewed literature from January 2010 to May 2025 across PubMed, Scopus, Web of Science, and IEEE Xplore. Included studies evaluated AI applications in plastic surgery using validated models and reported performance metrics. Quality assessment was performed using QUADAS-2, Newcastle-Ottawa Scale, and TRIPOD-AI criteria. A random-effects meta-analysis summarized pooled accuracy across domains.ResultsA total of 25 studies met inclusion criteria. Overall, AI achieved a pooled diagnostic accuracy of 88% (95% CI: 0.85–0.90; I2 = 32%). Postoperative evaluation showed the highest accuracy (90%), followed by preoperative planning (88%) and predictive modeling (86%). Convolutional Neural Networks (CNNs) and Artificial Neural Networks (ANNs) demonstrated strong performance in image-based and predictive tasks, respectively. However, fewer than 40% of studies reported external validation, and none included prospective clinical trials. Ethical concerns, limited data diversity, and methodological inconsistencies were prevalent.ConclusionThis study confirms AI's significant potential in plastic surgery for enhancing surgical precision and personalized care. However, clinical integration is hindered by inadequate validation, transparency, and demographic representation. Advancing the field requires standardized protocols, multicenter collaborations, and ethical frameworks to ensure safe and equitable deployment of AI technologies.